Penerapan Sistem Penomoran dalam Pengelolaan Majalah Sekolah - Mimin Trianjani; Zulfa Sofiana; Muhammad Arifin; Ade Rosad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
School magazines are publication media that function as a means of information, documentation, and student creativity development. In its management, a structured administrative system is needed so that each publication can be properly documented. This study aims to describe the implementation of numbering systems in school magazines and their benefits in supporting publication administration management. The research used a qualitative descriptive approach with data collection techniques in the form of observation, documentation, and literature study. The results showed that the numbering system helps managers identify each publication, facilitates archiving, and maintains the continuity of school magazine publications. In addition, the consistent implementation of numbering can improve publication professionalism and support digital archive management. Therefore, the numbering system becomes an important part in supporting effective and structured school magazine management.